Association of symptomatic gallstones and primary hyperparathyroidism: a propensity score-matched analysis. Issue 10 (9th August 2021) - Saito, Y; Takami, H; Abdelhamid Ahmed, A H; Nakao, A; Ho, K; Tokuda, T; Miyata, R; Randolph, G W; Ando, N
Abstract : If the prevalence of primary hyperparathyroidism (PHPT) in patients with symptomatic gallstones is higher than that in the general population, PHPT screening could reveal important clinical implications. We observed that the prevalence of PHPT in these patients was higher compared to that of healthy matched controls.